Research on food-related chronic diseases in Latin America and the Caribbean: Are we building the evidence for gender-equitable approaches? - Teralynn Ludwick; Daniela Neri (Pan American Health Organization, 2019)
Objectives. Gender continues to be largely neglected in the global response to the noncommunicable disease epidemic. The objectives of this study were to examine current practice and barriers faced by Latin American and Caribbean (LAC) researchers in addressing gender in research on healthy food environments, and to identify future topics for gender-sensitive and gender-transformative research. Methods. This study involved: 1) a descriptive, three-part survey to investigate to what extent LAC researchers are integrating gender considerations in research for healthier food environments and 2) a participatory workshop to coproduce ideas for future gender-sensitive and gender-transformative research. Results. Fifty-four participants, from 19 countries, attended the workshop. Of those 54, 41 of them responded to at least one section of the three-part survey, including with 26 of the 41 responding to the section on gender. Of these 26, 17 (65.4%) had collected sex-disaggregated data and 14 (53.8%) had conducted gender analysis in recent research on food environments. Few participants had integrated gender-related findings in their recommendations and solutions. Challenges included data and methodological limitations (e.g., lack of preexisting evidence, working with secondary data), knowledge and capacity gaps, subject sensitivity, and biases. Participants identified research topics for enhancing gender equity that included food preparation norms and domestic responsibilities; differential participation of women and men in food production, distribution, and retail; and employment and school policies. Conclusions. The findings from this study suggest that gender inequity is not being well addressed in food environment research from the LAC region. The analytical framework presented here can serve as an important starting point and resource for catalyzing future gender-transformative research. Complementary efforts are needed to overcome other challenges raised by the participating researchers, including capacity gaps, resource and data limitations, and publishing barriers.